Juvenile idiopathic arthritis in relation to perinatal and maternal characteristics: a case control study - Samantha W. Bell; Susan Shenoi; J. Lee Nelson; Parveen Bhatti; Beth A. Mueller (BMC, 2017)
Abstract Background Existing data on associations between maternal and early childhood exposures and juvenile idiopathic arthritis (JIA) risk is scant and inconsistent with previous studies showing potential role for prematurity, number of siblings and infections. We explored JIA and International League of Associations for Rheumatology (ILAR) JIA categories in relation to selected infant (birthweight, size-for-gestational-age, gestational age), and maternal (parity, delivery type, prior fetal loss) characteristics that may be markers for exposures related to two pathways (hygiene hypothesis, microchimerism) potentially associated with autoimmune disorder occurrence. Methods A case-control analysis with 1,234 JIA cases and 5,993 birth year-matched controls was conducted. Exposure information was obtained from WA state birth certificates. Multivariable logistic regression was used to estimate adjusted odds ratios (OR) and 95% confidence intervals (CI) for associations with maternal and early life exposures for JIA and JIA categories. Results Greater maternal parity was associated with a decreased OR for JIA (most marked for persistent oligoarticular JIA, OR 0.32, 95% CI 0.15; 0.71, p for trend = 0.0001). Prior fetal loss (except for oligoarticular JIA) was associated with an increased OR for JIA. Prematurity was associated with increased risk of enthesitis related arthritis (OR 1.9, 95% CI: 1.3-2.9) and rheumatoid factor positive polyarticular JIA (OR 2.2, 95% CI: 1.0-4.8). Conclusions We observed associations of selected maternal factors with JIA, some of which varied across JIA categories. The findings of decreased ORs for JIA in relation to greater maternal parity may be consistent with the hygiene and microchimerism hypotheses. Future studies with biomarkers relevant to these hypotheses will help elucidate any associations.